2005
DOI: 10.1262/jrd.51.37
|View full text |Cite
|
Sign up to set email alerts
|

First Messenger Regulation of Mammalian Sperm Function via Adenylyl Cyclase/cAMP

Abstract: Abstract. When released into an appropriate environment, mammalian spermatozoa begin to capacitate and then continue until fully capacitated and able to fertilize. During capacitation in vitro, some cells 'over-capacitate' and undergo spontaneous acrosome reactions; this would be highly undesirable in vivo since already acrosome-reacted spermatozoa are non-fertilizing. Recent studies have revealed that seminal plasma contains several small molecules that bind to specific receptors on the sperm plasma membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…These changes can alter ion transport for instance of Ca 2þ and HCO 2 3 itself, thus activating sAC. It has been proposed that sAC is mainly responsible for the cAMP changes during capacitation (Esposito et al 2004, Hess et al 2005, although a transmembrane AC may also contribute (Fraser et al 2005; Fig. 3).…”
Section: Sperm Capacitationmentioning
confidence: 99%
“…These changes can alter ion transport for instance of Ca 2þ and HCO 2 3 itself, thus activating sAC. It has been proposed that sAC is mainly responsible for the cAMP changes during capacitation (Esposito et al 2004, Hess et al 2005, although a transmembrane AC may also contribute (Fraser et al 2005; Fig. 3).…”
Section: Sperm Capacitationmentioning
confidence: 99%
“…The most widely accepted functional definition of in vitro capacitation is acquisition of ability to undergo acrosome reaction in response to a biological agonist, such as zona pellucida or progesterone. Studies on sperm incubated under capacitating conditions have revealed numerous biochemical and physiological changes that accompany the process including an efflux of plasma membrane cholesterol, an increase in the activity of adenylate cyclase (both soluble and membrane localized), elevated levels of cAMP and protein kinase A (PKA) activity, a rise in intracellular pH, hyperpolarization of membrane potential and increased serine/ threonine and tyrosine phosphorylation of some proteins (Tash & Means 1983, Leclerc et al 1996, Cross 1998, Osheroff et al 1999, Lefièvre et al 2002, O'Flaherty et al 2004, Fraser et al 2005. These observations provide useful indicators of the occurrence of capacitation in spermatozoa in vitro, but it is still far from clear how the various events relate to each other or whether all of them must occur for the acquisition of fertilization competence to occur.…”
Section: Events Associated With Sperm Capacitationmentioning
confidence: 99%
“…These observations provide useful indicators of the occurrence of capacitation in spermatozoa in vitro, but it is still far from clear how the various events relate to each other or whether all of them must occur for the acquisition of fertilization competence to occur. It is likely that sperm possess the ability to regulate the signalling pathways involved in capacitation, thus minimizing over-capacitation and premature acrosome reaction , Ecroyd et al 2004, De Jonge 2005, Fraser et al 2005), but it is not clear to what extent the changes that have been observed in capacitating cells are reversible and whether they are capacitation endpoints or part of the capacitation process (such that reversal does not prevent subsequent induction of acrosome reaction).…”
Section: Events Associated With Sperm Capacitationmentioning
confidence: 99%
“…In reacting to the sperm, HOS test is an influx of water into the interior of cells and consequent alteration of cell volume and plasma membrane and causes a folding of the flagellum of sperm that are the biochemical integrity of the plasma membrane (Revel and Mrode, 1994). The processes of staining, the acrosome reaction and fertilization require a biochemically active membrane (Fraser et al, 2005), and relationships between high fertility and the HOS test samples of frozen bull semen was found in artificial insemination programs (Revell and Mrode, 1994;Correa et al 1997;Bacinoglu et al, 2008). This study aimed at evaluating the relationship between physical and morphological semen features with the HOS test in raw semen of adult Nelore bulls classified as sound and unsound for breeding.…”
Section: Introductionmentioning
confidence: 99%